Apocalipsis para principiantes - Dickner, Nicolas, 1972-; Feliu, Luisa; Dickner, Nicolas, 1972- (Madrid : Siruela, 2014)
Best friends and would-be lovers Hope Randall and Mickey Bauermann find comfort in each other as Hope awaits the end of the world habitually foretold by her family's long line of erroneous visions. When the truth about her family comes to light, Hope leaves Mickey behind to forge a new path ... alone.
Online resource; title from ePub title page (Digitalia, viewed April 1, 2016)
Keywords: Visions -- Fiction; Puberty -- Fiction; End of the world -- Fiction; Families -- Fiction; Mothers and daughters -- Fiction; Man-woman relationships -- Fiction; Romance fiction; Science fiction; Apocalyptic fiction; Electronic books